Toward Better Weighting of Anchors - Hawking, David; Upstill, Trystan; Craswell, Nick (Proceedings of ACM SIGIR 2004 (poster abstract), 2004)
Okapi BM25 scoring of anchor text surrogate documents has been shown to facilitate effective ranking in navigational search tasks over web data. We hypothesize that even better ranking can be achieved in certain important cases, particularly when anchor scores must be fused with content scores, by avoiding length normalisation and by reducing the attentuation of scores associated with high tf . Preliminary results are presented.
://research.microsoft.com/users/nickcr/pubs/hawking_sigir04poster.pdf